Construction of a Single Chain Variable Fragment Against Mcf-7 Breast Cancer Cells - Ahmad, Zuhaida Asra (2008)
Recombinant antibody cloning and phage display technologies can be employed to produce and isolate single-chain antibodies (scFv) specifically against antigen of interest. The aims of this study are to construct single chain variable fragment (scFv) towards MCF-7 breast cancer cells and to characterize scFv antibodies that interacts with MCF-7. Initially, mRNA was extracted from previously well-characterized monoclonal antibody (C3A8) against MCF-7. The genes encoding heavy (VH) and light (VL) chains were amplified, linked in VH-VL orientation via PCR and cloned into a pCANTAB 5E phagemid vector. The protein was then expressed in a supE strain of E. coli TG1. Phage particles displaying scFv were panned against MCF-7 and the selected clones were further used for infecting non-suppressor strain, E. coli HB2151. The scFv antibodies expressed were characterized by enzyme-linked immunosorbent assay (ELISA) and immunoblotting. As demonstrated by ELISA result, the scFv antibodies could strongly bind to MCF-7 breast cancer cells. It retained the binding capacity of its parental C3A8 monoclonal antibody. Clone B7 was expressed mainly as soluble periplasmic protein. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis of the recombinant antibody revealed a protein with apparent molecular weight of approximately 32 kDa. Nucleotide sequence analysis of C3A8 scFv showed high homology (99%) with published single chain antibody against rice stripe virus protein P20 [synthetic construct]. In conclusion, the recombinant antibody technology is an effective approach in the development of scFv antibody for the next generation of immunotherapy reagents especially towards MCF-7 breast cancer cells.